Pemberdayaan Petani dan UMKM Melalui Inovasi Budidaya Labu Siam di Desa Cipasang Cibugel Sumedang - Arifin; Nunung Sondari; Yusfita Yusuf (UNISBA Press, 2024)
Abstract. Siamese pumpkin cultivation in Cipasang Village, Cibugel District, Sumedang Regency is seen as one of the leverage to reduce stunting and poverty. Siamese pumpkin contains various nutrients including vitamin B complex and folate, and is low in calories. In addition, these vegetables contain antioxidants, flavonoids, and other compounds that function to optimize children's cognitive development. One of the challenges in Siamese pumpkin cultivation in Cipasang Village is post-harvest sales where farmers often fall victim to middlemen because of low prices. Therefore, efforts are needed to develop the added value of chayote products through community service. The targets of community empowerment activities are farmers and MSMEs related to siamese pumpkin cultivation. Community service activities are carried out through the stages of preliminary study, implementation, and evaluation. The implementation stages start from making demplots on partner-owned land to prepare for seeding and planting chayote, planting as many as 50 plants as a pilot for residents, and introducing processed siamese pumpkin products. The yield of the plant showed good growth and began the production of fruits of fairly good size. Processed cultivation innovation in the form of flour and used as raw material for various finished preparations such as cakes and crackers. Abstrak. Budidaya labu siam di Desa Cipasang Kecamatan Cibugel Kabupaten Sumedang dipandang sebagai salah satu daya ungkit untuk menurunkan angka stunting dan angka kemiskinan. Labu siam mengandung berbagai nutrisi antara lain vitamin B kompleks dan folat, serta rendah kalori. Selain itu, sayuran ini mengandung antioksidan, flavonoid, dan senyawa lainnya yang berfungsi mengoptimalkan perkembangan kognitif anak. Salah satu tantangan dalam budidaya labu siam di Desa Cipasang adalah penjualan pasca panen dimana petani sering menjadi korban para tengkulak karena harga yang murah. Oleh karena itu diperlukan upaya mengembangkan nilai tambah produk labu siam melalui pengabdian masyarakat. Sasaran kegiatan pemberdayaan masyarakat adalah petani dan UMKM terkait budidaya labu siam. Kegiatan pengabdian masyarakat dilakukan melalui tahapan studi pendahuluan, pelaksanaan, dan evaluasi. Tahapan pelaksanaan mulai dari pembuatan demplot di lahan milik mitra untuk persiapan penyemaian dan penanaman labu siam, penanaman sebanyak 50 tanaman sebagai percontohan bagi warga, dan pengenalan produk olahan labu siam. Hasil tanaman menunjukkan pertumbuhan yang baik dan mulai produksi buah dengan ukuran yang cukup baik. Inovasi budidaya olahan berupa tepung dan digunakan sebagai bahan baku aneka olahan jadi seperti kue dan kerupuk.